Compare the Insuline Resistance of Diabetic Type 2 Men and Women Subjects - Arslan Sajjad, Malik Muhammad Toqeer, Sana Mujeeb, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Diabetic type 2 men and women are the subjects of this research, which aims to assess insulin resistance. Study Design: Observational/Prospective Place and Duration: Rawalpindi Medical University, Holy Family Hospital. Nov 2019-April 2020 Methods: There were 100 patients of both genders in this research. Patients ranged in age from 20 to 70. After obtaining written permission, we collected demographic data on each patient, including age, gender, and BMI. Patients' fasting insulin and glucose levels were evaluated. IRI (insulin resistance indices) were calculated using HOMA-IR 1 (insulin resistance metre). SPSS 23.0 was used to analyze all of the data. Results: We found that patients' mean age was 36.13± 4.15, with an average BMI of 27.15±8.65 kg/m2. Males accounted for 42 of the 100 patients, while females accounted for 58 of the 100 patients. Comparing men and girls, serum glucose levels in the males were higher than those in the females at 13.35 ±6.88 mmol/L and 9.12 ± 11.45 mmol/L, respectively, and insulin resistance was higher in the males at 7.45±8.121and 6.13±4.32 in females. In terms of gender, there was no statistically significant difference (p value 0.004). Conclusion: In this research, we found that increasing insulin sensitivity was more challenging in males. This might indicate that males who are insulin-resistant may need to take a more active role in preventing the development of metabolic or diabetic disorders.